2015
DOI: 10.1016/j.jce.2014.10.001
|View full text |Cite
|
Sign up to set email alerts
|

The labor supply of self-employed workers: The choice of working hours in worker co-ops

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…These results are consistent with other findings that LMFs generally respond to shocks by maintaining stable employment levels while allowing incomes to vary, rather than adjusting the quantities of inputs and outputs (Craig and Pencavel , Pencavel and Craig , Pencavel et al. , Burdín and Dean , Pencavel ). I regard the empirical results on LMF objective functions as disconfirming the WDV hypothesis.…”
Section: The Present (1993–2017)supporting
confidence: 91%
“…These results are consistent with other findings that LMFs generally respond to shocks by maintaining stable employment levels while allowing incomes to vary, rather than adjusting the quantities of inputs and outputs (Craig and Pencavel , Pencavel and Craig , Pencavel et al. , Burdín and Dean , Pencavel ). I regard the empirical results on LMF objective functions as disconfirming the WDV hypothesis.…”
Section: The Present (1993–2017)supporting
confidence: 91%
“…This proves that partners also consider other objectives besides net income. Notable to this respect are the works of Craig and Pencavel (1993), Burdin and Dean (2009) and Pencavel (2015), which introduce employment in the production function to contrast the weight partners grant to maintaining employment as opposed to partner income. This result coincides with empirical studies showing that cooperatives have a greater capacity to create employment under depressed economic conditions.…”
Section: Theoretical Debatementioning
confidence: 99%
“…Empirical evidence suggests that longer working hours tend to decrease workers' productivity. In a recent study, Pencavel (2015) used data from the production of munitions in Britain during the First World War and found that employees working long hours experienced fatigue and were less productive. Similarly, Collewet and Sauermann (2017) studied the productivity of call center agents and found that an increase in their working hours led to an increase in the average handling time for calls.…”
Section: Evidence On Multiple Job Holdingmentioning
confidence: 99%